SOCIO-COGNITIVE DIMENSIONS OF DEVELOPMENTALIST DISCOURSE: A CRITICAL DISCOURSE ANALYSIS OF INDONESIAN MEDIA REPRESENTATIONS OF THE IBU KOTA NUSANTARA RELOCATION - Aura Rahma Azzahra (INSPIRATION: Instructional Practices in Language Education, 2026)
The relocation of Indonesia’s national capital from Jakarta to Ibu Kota Nusantara (IKN) in East Kalimantan has emerged as a prominent developmentalist project that embodies competing visions of national progress, environmental sustainability, and political legitimacy. This study aims to examine how Indonesian online media construct and contest the meaning of the IKN project through discourse. The research employs Critical Discourse Analysis (CDA) using Teun A. Van Dijk’s socio-cognitive approach, which integrates textual structures, social cognition, and power relations. A qualitative case study design is applied to news articles published by Tempo.co and Kompas.com between early 2024 and early 2025. The analysis is conducted at three levels: macrostructure (global themes), superstructure (news schemata), and microstructure (lexical, syntactic, and rhetorical features), while also considering mental models and ideological positioning. The findings indicate a consistent pattern of discursive divergence between the two media outlets. Kompas.com predominantly constructs IKN through a developmentalist discourse emphasizing national progress, modernization, and economic opportunity, thereby legitimizing state developmentalist ideology. In contrast, Tempo.co constructs a critical narrative that emphasizes environmental degradation, fiscal risk, and democratic deficits, functioning as discursive resistance to state power. The study concludes that Indonesian media do not merely report the IKN relocation but potentially contribute to the formation of public mental models and social representations of national development. The research implies that critical media literacy is essential for democratic accountability, as large-scale state projects are increasingly legitimized or contested through strategic language use in digital media.